"Analysing the Role of Financial Technology (Fintech) In Enhancing Access to Credit for SMES: A Cross-Country Study" - Sanjeev Kumar, Vivek Bhatia, (European Economic Letters (EEL), 2024)
There are substantial obstacles for small and medium businesses (SMEs) to get conventional financial services, especially loans, despite their importance as development engines for the economy. Innovative solutions to these problems have emerged with the rise of financial technology (FinTech), which makes use of developments like alternative credit scoring techniques, blockchain, and peer-to-peer lending. With a focus on established, rising, and developing countries, this research examines how FinTech might improve the availability and performance of loans for small and medium-sized enterprises (SMEs). The study uses quantitative methodologies such as regression analysis and Structural Equation Modelling (SEM) to look at how FinTech adoption affects SMEs' operational efficiency, client acquisition, profit margins, and revenue growth. Research shows that small and medium- sized enterprises (SMEs) who use FinTech see a considerable improvement in their performance, with adopters outperforming non-adopters in terms of operational efficiency (80.5) and revenue growth (15.8%). Digital literacy is seen as a significant factor in the efficient utilisation of FinTech, while regulatory backing and technical infrastructure are considered as essential facilitators of FinTech adoption. In terms of economic background, the report shows that developed countries have the greatest adoption rates of FinTech and that developing nations have a lot of room to expand. Fostering regulatory frameworks and offering incentives to promote innovation and adoption of FinTech are practical consequences for policymakers. By using FinTech technologies, financial institutions may extend their services to small and medium-sized enterprises (SMEs) who are currently underserved, hence enhancing financial inclusion. In order to stay competitive, SMEs should prioritise digital preparedness and use FinTech solutions, according to recommendations. In its last section, the report suggests directions for further investigation, such as studying the impact of FinTech on the viability of SMEs in the long run and looking into the sector-specific uses of cutting-edge technology like blockchain and artificial intelligence. This study adds to what is already known about the relationship between financial technology (FinTech) and small and medium-sized enterprise (SME) funding, and it provides useful information to those who are working to close the credit gap and promote economic development for everyone.